Fabrication of Sandwich-structured Si Nanoparticles-Graphene Nanocomposites for High-performance Lithium-ion Batteries. (1st July 2015) - He, Dafang; Bai, Fengjuan; Li, Lixian; Shen, Liming; Kung, Harold H.; Bao, Ningzhong
Graphical abstract: Highlights: Sandwich-structured Si nanoparticles-Graphene nanocomposites were fabricated. The method combines magnesiothermic reduction, freeze-drying, and thermal reduction. The nanocomposite shows a 746 mAh g −1 reversible capacity after 160 cycles. The nanocomposite's specific capacity is superior to that of graphite and pure Si. This novel method provides a low-cost alternative to prepare Si-based anodes. Abstract: A novel method was developed to synthesize ordered sandwich-structured magnesiothermo-reduced Si nanoparticles (MR-Si NPs)-thermally reduced graphene oxide (TRGO) nanocomposites that combines magnesiothermic reduction, freeze-drying, and thermal reduction. The MR-Si NPs were dispersed into ordered graphene oxide (GO) layers with the aid of sonication. This MR-Si@TRGO composite structure was retained by freeze-drying and followed by thermal reduction. The key features of the nanocomposites, including nanoparticle crystal phase, size, and dispersity on the TRGO matrix, could be controlled by tuning reaction conditions such as reduction temperature and duration. The influence of the weight ratio of active materials: conductive agent: binder, the types of binder, and the content of electrolytes on the electrochemical performance as an anode in lithium-ion batteries was systematically investigated. The electrode fabricated using the MR-Si@TRGO nanocomposites under optimized conditions (80:10:10 for the weight ratio of MR-Si@TRGO: acetylene black: CMC; the electrolyte containing 5 v% vinylene carbonate) exhibited a reversible capacity of 746 mAh g −1 after 160 cycles at 1000 mA g −1, which is substantially higher than 701 mAh g −1 after 120 cycles for the MR-Si@TRGO in the absence of vinylene carbonate, 330 mAh g −1 for commercial graphite reported, and 10 mAh g −1 for pure MR-Si NPs tested at 200 mA g −1 with a weight ratio of 50:30:20 optimized for active materials: acetylene black: PVDF.